2014
DOI: 10.4238/2014.february.14.7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of warm day and cool night conditions induced flowering-related genes in a Phalaenopsis orchid hybrid by suppression subtractive hybridization

Abstract: ABSTRACT. The influence of warm day and cool night conditions on induction of spikes in Phalaenopsis orchids has been studied with respect to photosynthetic efficiency, metabolic cycles and physiology. However, molecular events involved in spike emergence induced by warm day and cool night conditions are not clearly understood. We examined gene expression induced by warm day and cool night conditions in the Phalaenopsis hybrid Fortune Saltzman through suppression subtractive hybridization, which allowed identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
(39 reference statements)
1
4
0
Order By: Relevance
“…These results suggest that roots might play an important role before flowering transition in Phalaenopsis hybrid Fortune Saltzman and might be involved in the flowering transition and development signaling pathway. Compared with that in the apical leaves under warm daily temperatures, the expression of PhFT was obviously higher under warm day and cool night conditions; such conditions induced 0-3-mm long spikes and gradually reduced during spike development (Li et al, 2014). The mRNA expression of PhFT during flowering was remarkably higher in the flower buds at the different developmental stages (Figure 5), similar to observations for FT in Oncidium Gower Ramsey (OnFT) (Hou and Yang, 2009).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…These results suggest that roots might play an important role before flowering transition in Phalaenopsis hybrid Fortune Saltzman and might be involved in the flowering transition and development signaling pathway. Compared with that in the apical leaves under warm daily temperatures, the expression of PhFT was obviously higher under warm day and cool night conditions; such conditions induced 0-3-mm long spikes and gradually reduced during spike development (Li et al, 2014). The mRNA expression of PhFT during flowering was remarkably higher in the flower buds at the different developmental stages (Figure 5), similar to observations for FT in Oncidium Gower Ramsey (OnFT) (Hou and Yang, 2009).…”
Section: Discussionsupporting
confidence: 73%
“…We obtained one full-length cDNA (JK720571, 809 bp) from a suppression subtractive hybridization cDNA library of Phalaenopsis hybrid Fortune Saltzman spikes induced by warm days and cool nights in a previous study (Li et al, 2014). BLASTx search showed that the cDNA sequence was highly homologous to the FT proteins of C. goeringii (accession No.…”
Section: Characterization Of the Cdna Sequence Of Phftmentioning
confidence: 99%
See 1 more Smart Citation
“…The result showed that, in addition to FT , LFY , APETALA1 ( AP1 ) and OVEREXPRESSION OF CONSTANS 1 ( SOC1 ) homologs, genes involved in GA biosynthesis were also up-regulated by low ambient temperature. Another expression analysis using Phalaenopsis Fortune Saltzman found that transcripts of KNOX1 , R2R3-like MYB , adenosine kinase 2, S-adenosylmethionine synthetase, dihydroflavonol 4-reductase, and naringenin 3-dioxygenase were accumulated at a higher level in spikes grown under warm day/cool night (28 °C/21 °C) compared with those grown at daily warm temperature (28 °C/26 °C) under natural light conditions (Li et al, 2014).…”
Section: Floral Transition Of Orchidsmentioning
confidence: 99%
“…However, we cannot exclude the possibility that the pavement for the PaFT1 movement to the dormant/juvenile buds is not available. Based on the transcriptomic analyses of Phalaenopsis orchids, KNOX1 , SOC1 and FVE genes are induced by low ambient temperature (Sun et al, 2012; Li et al, 2014; Huang et al, 2016) although Dendrobium KNOX1 gene is down-regulated by low ambient temperature (Yu and Goh, 2000a; Yu et al, 2000). Thus, the role of KNOX1 in floral transition of Phalaenopsis needs to be further examined.…”
Section: Floral Transition Of Orchidsmentioning
confidence: 99%